Capacity constraints and time allocation in public health clinics. (14th January 2020) - Harris, Matthew C.; Liu, Yinan; McCarthy, Ian
Summary: Unlike in the production of most goods, changes in capacity for labor‐intensive services only affect outcomes of interest insofar as service providers change the way they allocate their time in response to those capacity changes. In this paper, we examine how public sector service providers respond to unexpected capacity constraints in the specific context of public health clinics. We exploit an exogenous reduction in public health clinic capacity to quantify the trade‐off between patients treated and time spent with each patient, which we treat as a proxy for a quality versus quantity decision. We provide evidence that these small and generally insignificant effects on nurse time favor public sector employees prioritizing quality of each interaction over clearing the patient queue.